2012
DOI: 10.1371/journal.pone.0035479
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Impact of Integrating HIV and Outpatient Health Services on Patient Waiting Times in an Urban Health Clinic in Zambia

Abstract: BackgroundRapid scale up of HIV treatment programs in sub-Saharan Africa has refueled the long-standing health policy debate regarding the merits and drawbacks of vertical and integrated system. Recent pilots of integrating outpatient and HIV services have shown an improvement in some patient outcomes but deterioration in waiting times, which can lead to worse health outcomes in the long run.MethodsA pilot intervention involving integration of outpatient and HIV services in an urban primary care facility in Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
(34 reference statements)
2
19
0
Order By: Relevance
“…Given that providers were interviewed one year after FP/HIV integration began, the challenges associated with implementing new protocols may have been more acutely felt. Further research is needed to evaluate how to address obstacles like human resource shortages in order to capitalize on the service delivery efficiencies that can be produced by integration efforts (Topp et al, 2013; Deo et al, 2012) and that could be especially beneficial in resource-constrained settings.…”
Section: Discussionmentioning
confidence: 99%
“…Given that providers were interviewed one year after FP/HIV integration began, the challenges associated with implementing new protocols may have been more acutely felt. Further research is needed to evaluate how to address obstacles like human resource shortages in order to capitalize on the service delivery efficiencies that can be produced by integration efforts (Topp et al, 2013; Deo et al, 2012) and that could be especially beneficial in resource-constrained settings.…”
Section: Discussionmentioning
confidence: 99%
“…Wait times increased from 91 to 127 minutes in a Zambian clinic due to staff and patient flow problems after integration of HIV services with primary healthcare. 161 Longer wait times could increase loss to follow-up or exacerbate stigma, 162-164 and TB transmissions could even be increased. 69,165 Staff training and program quality might be less effective or more costly when multiple interventions are provided together.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…However, adoption of such models may come at a cost. In the Zambia study, waiting times increased for all patients at newly integrated sites, delays largely attributed to inadequate staffing levels and longer breaks between consecutive patient visits (20). Investigators in Mozambique found higher rates of attrition among patients attending integrated clinics for more than 6 months (hazard ratio [HR]: 1.75, 1.04–2.94) (21).…”
Section: Why Integrate?mentioning
confidence: 99%